Aotearoa New Zealand in the global theatre marketplace : travelling theatre - Wenley, James (London: Routledge, 2021)
"Aotearoa New Zealand in the Global Theatre Marketplace is a case study of how work from one nation has attempted to tour, represent and market itself in the global theatre industry. Against challenging market conditions, how has theatre from Aotearoa New Zealand attempted to stand out, differentiate itself, and get seen by audiences overseas? Aotearoa New Zealand will primarily focus on examples of New Zealand theatrical work toured and performed internationally under the accelerated globalised conditions over the last thirty years. The analysis of specific plays and productions will be used to develop two main conceptual areas. The first is the negotiation of international theatrical marketplaces by non-local work and companies The second primary conceptual concern is the negotiation of national and cultural identity in the performance and reception of theatrical works.In following New Zealand theatre overseas, this book aims to give an outsider insight into a range of geographic theatrical marketplaces, including the Edinburgh Festival Fringe, London, North America, Asia and the Pacific Arts Festivals. Ultimately, James Wenley's study will raise questions about the mobility/portability of theatre, and the potential of theatre to be a means for cross-cultural conversation and understanding for audiences to see the lives of others onstage, and find resonances within their own contexts"--
Includes bibliographical references and index.
Keywords: Theater -- New Zealand; New Zealand drama; Performing arts